Design of a masters course (MBA) from the perspective of Project Management - Campanario, Milton de Abreu; Maccari, Emerson Antonio; Silva, Marcello Muniz da; Santana, Sibelle Gomes de (Review of Business Management, 2009)
The aim of this paper is to present the design and development of a masters course (MBA) from the perspective of theories and techniques of project management, based on the findings of our experience at the Universidade Nove de Julho - UNINOVE. The relevance of this study is guided by the use of the concepts of project management for the development of a project masters degree, with its structural criteria, characteristics and critical factors, including CAPES accreditation (Coordenadoria de Aperfeiçoamento de Pessoal de Nível Superior). The research method used was a single case study of a masters course in Project Management, up to now it has only been dealt with specialized courses. We used the Project Management classical steps in the development of this MBA course: initiation, planning and design, executing, monitoring controlling and closing. Key words: Project management. PMBOK. MBA. CAPES.